2018
DOI: 10.1139/apnm-2017-0449
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training-induced decrease in central arterial compliance is associated with decreased subendocardial viability ratio in healthy young men

Abstract: High-intensity resistance training decreases central arterial compliance (CAC). Subendocardial viability ratio (SEVR) is a useful tool that reflects the balance between coronary perfusion and left ventricular afterload. Animal studies have demonstrated that decreased CAC is associated with SEVR deterioration. Therefore, resistance training-induced decrease in CAC may be associated with changes in SEVR. The objective of the present study was to investigate the association between SEVR and CAC using both cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Low BI indicates decreased subendocardial perfusion (5). We and other researchers have reported that high-intensity resistance exercise and regular high-intensity resistance exercise reduce BI (14,29). Furthermore, we revealed that a decrease in central arterial compliance (i.e., increased central arterial stiffness) induced by regular high-intensity resistance exercise was correlated with BI in young men (29).…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Low BI indicates decreased subendocardial perfusion (5). We and other researchers have reported that high-intensity resistance exercise and regular high-intensity resistance exercise reduce BI (14,29). Furthermore, we revealed that a decrease in central arterial compliance (i.e., increased central arterial stiffness) induced by regular high-intensity resistance exercise was correlated with BI in young men (29).…”
Section: Introductionsupporting
confidence: 54%
“…We and other researchers have reported that high-intensity resistance exercise and regular high-intensity resistance exercise reduce BI (14,29). Furthermore, we revealed that a decrease in central arterial compliance (i.e., increased central arterial stiffness) induced by regular high-intensity resistance exercise was correlated with BI in young men (29). Therefore, it is considered that the increased central arterial stiffness with high-intensity resistance exercise deteriorates subendocardial perfusion.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…The pressure wave at the carotid artery was recorded with the applanation tonometry sensor (TU-100; Colin Medical Technology, Aichi, Japan). Using the general transfer function-based pulse wave analysis software (Sphyg-moCor version 8.0; AtCor Medical, Australia), various parameters of the aortic pressure wave were computed from the carotid pressure waveform calibrated with MAP and brachial DBP, as we previously reported 21,22) . Briefly, aortic SBP and DBP were obtained as the maximum and minimum of the aortic pressure waveform, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, since resistance training has been shown to have detrimental effects on central arterial compliance including PWV [141][142][143] , while evidence states the opposite 144 , it would be interesting to see an exercise intervention comparing the effects of HIIT versus resistance training on parameters of central arterial compliance and stiffness. We also did not employ a nutritional intervention or calorie restriction study, which has shown beneficial effects on the general population 145 .…”
Section: Future Directionsmentioning
confidence: 99%